The Role of Sustainable Regional Development in Increasing the Competitiveness Strategy of UMKM Enterprises in Banyuwangi Regency - Enggita Salsabila; Gusti Ayu Wulandari; Izza Savina Firdaus (International Journal of Society and Law, 2024)
This study aims to analyze the competitiveness of Micro, Small, and Medium Enterprises (UMKM) in Banyuwangi Regency and formulate strategies to maintain their competitiveness through the sustainable role of the local government. SWOT analysis is used to identify the internal and external factors faced by UMKM (Micro Small Medium Enterprises). The results show that the strategies that can be pursued include developing clusters/centers of leading UMKM (Micro Small Medium Enterprises), increasing product value-added and differentiation, and improving human resource capacity. The role of the local government is key in supporting the implementation of these strategies through providing access to capital, facilitating promotion and marketing, and comprehensive fiscal incentives. The joint efforts of UMKM (Micro Small Medium Enterprises) actors and local government are expected to increase the competitiveness of UMKM (Micro Small Medium Enterprises) and support inclusive and sustainable regional economic growth.